Hubungan Antara Tekanan Darah Dengan Nilai Ankle Brachial Index Pada Lansia - Rifaudin, Destria; , Isnaini Herawati, S.Fis, S.Pd., M.Sc (2016)
Background: The blood pressure is very important in blood circulation and is always necessary as a force to the blood flow in the arteries, arterioles, capillaries, and the venous system to form stable blood flow. Heart pumping activities takes place by means of holding the contraction and relaxation, result in changes in blood pressure in the circulatory system. Physiologically when arterial constrict (shrinking) peripheral resistance increased, while when the artery dilated (widening) peripheral resistance decreased. If impaired, then it effect the blood pressure, Ankle Brachial Index (ABI) examination is intended to identify peripheral artery disease by comparing the systolic blood pressure of the ankle to brachial systolic blood pressure. Objective: To determine the relationship between blood pressure and Ankle Brachial Index values in the elderly. Methods: observational study with cross sectional analytic study design aims to determine the relationship between blood pressure based on the value of systolic and diastolic with ABI values, with a sample size of 83 people. Data were analyzed using univariate test with frequency distribution table and bivariate test using chi-square test. Results: The relationship between blood pressure with ABI values in the elderly based on systolic value results in (p = 0.00; OR = 3.88; CI 95% lower 1.50; upper 10.03). While the relationship between blood pressure ABI values in the elderly based on diastole value results in (p = 0.00; OR = 4.73; CI 95% lower 1.85; upper 12.14). Conclusion: There is a relationship between blood pressure based on systolic value and diastolic value with the ABI value in the elderly. Keywords: ABI Value, Blood pressure, the elderly